Surface morphology, spectroscopy, optical and conductivity properties of transparent poly(9-vinylcarbazole) thin films modified with graphene oxide - Aydin, H.; Gündüz, Bayram; Aydin C. (Elsevier Ltd, 2019)
In this work, we synthesized the graphene oxide by Hummers method and prepared poly-N-vinylcarbazole (PVK)/graphene oxide (GO) nanocomposites. We investigated the SEM images, FTIR and UV spectroscopy and ac conductivity properties of PVK:wt% (0, 1, 5, 10, 15%) GO nanocomposites thin films. The PVK and PVK/GO nanocomposites are dominant in near ultraviolet region. The absorption band edge of the films of the PVK/GO nanocomposites varies from 3.077 to 3.175 eV, while the allowed optical band gap of the 0, 1, 5, 10 and 15% wt. GO + PVK nanocomposites varies from 2.97 to 3.30 eV. The optical band gap and refractive indices of the PVK can be changed with increasing the percentage by weight of graphene oxide. The single oscillator energy varies from 3.358 to 3.670 eV, while the dispersion energy varies from 6.404 to 6.970 eV. The graphene oxide has an important effect on the ac conductivity of the PVK. Obtained results show that the PVK material modified with graphene oxide is promising for electronic, optical and optoelectronic technology. © 2019 Elsevier B.V.
Keywords: Graphene oxide; Optical properties; Organic nanocomposites; Oscillator energy; Poly(9-vinylcarbazole)